All in the Family : State Capture in Tunisia - Rijkers, Bob; Freund, Caroline; Nucifora, Antonio (World Bank, Washington, DC, 2014)
Understanding state-business relationships and how they have shaped the institutional architecture of countries in the Middle East and Northern Africa (MENA) is crucial for the identification of systemic vulnerabilities and reform priorities. In this paper, the authors examine the relationship between regulation and the business interests of President Ben Ali and his family, using unique firm-level data from Tunisia for 1994 to 2010, and document how Tunisia s investment policy was abused to serve the president s family s private interests. In spite of widespread recognition of its importance, empirical evidence on state capture has been limited by a lack of data. To redress this lacuna, the authors merge data on investment regulations with balance sheet and firm-level census data in which 220 firms owned by the Ben Ali family are identified. The data set assembled allows identifying the relationship between investment policies and the business interests of Tunisia's politicians. Tunisians today literally continue to pay the price of privileges extended to an elite group of entrepreneurs. Reform efforts have not yet resulted in an opening up of economic opportunities for all, which is unfortunate since this was one of the central demands of those who took the streets a little over three years ago.